2021
DOI: 10.1007/s00259-021-05551-5
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG PET-CT in patients with DLBCL treated with CAR-T cell therapy: a practical approach of reporting pre- and post-treatment studies

Abstract: Purpose: The introduction of CD19-speci c chimeric antigen receptor T-cell therapy (CAR-T) for treatment of relapsed/refractory diffuse large B cell lymphoma (R/R DLBCL) gives hope to patients with otherwise dismal prognosis. Therapy outcomes depend, however, on selection of patients and on accurate early identi cation of non-responders. Patients treated with CAR-T usually undergo [ 18 F]FDG PET-CT at time of decision (TD), time of CAR-T transfusion (TT), one month (M1) and three months (M3) post therapy. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…4 The usefulness of 18 F-FDG PET/CT in predicting the efficacy of CAR-T therapy in refractory non-Hodgkin lymphoma has been demonstrated. [5][6][7][8][9] Pseudoprogression detected by 18 F-FDG PET/CT after CAR-T therapy has also been reported. However, the findings of hyperprogression on 18 F-FDG PET/CT are rarely reported.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…4 The usefulness of 18 F-FDG PET/CT in predicting the efficacy of CAR-T therapy in refractory non-Hodgkin lymphoma has been demonstrated. [5][6][7][8][9] Pseudoprogression detected by 18 F-FDG PET/CT after CAR-T therapy has also been reported. However, the findings of hyperprogression on 18 F-FDG PET/CT are rarely reported.…”
Section: Figurementioning
confidence: 85%
“…Reported hyperprogression incidence on checkpoint inhibitors varied between 2.5% and 29.4% of all responses 4 . The usefulness of 18 F-FDG PET/CT in predicting the efficacy of CAR-T therapy in refractory non-Hodgkin lymphoma has been demonstrated 5–9 . Pseudoprogression detected by 18 F-FDG PET/CT after CAR-T therapy has also been reported.…”
mentioning
confidence: 98%
“…It has been shown in ZUMA-1 and JULIET trials that reaching complete metabolic response (CMR) or partial metabolic response (PMR) according to Lugano criteria three months after infusion is predictive of sustained response and had similar outcome 1,3 . Although the median time to response is around one month in pivotal trials and real-world experiences 1,2,4,7 , the prognostic value of PET assessment after CAR T-cells infusion is under investigation 10 , and the conversion rate of response from one month to three months post CAR T-cells not fully documented.…”
Section: Cd19-specific Chimeric Antigenic Receptor T-cells (Car T-cel...mentioning
confidence: 99%
“…A lower tumor burden and/or lower tumor FDG uptake have been linked to better outcomes. An early metabolic response after treatment has also proved predictive of therapy success, assessed visually [ 13 , 16 ] or semi-quantitatively using SUV max [ 12 , 13 , 15 ]. In general, the studies performed are however small and mixed results have been reported in terms of which predictive metric to use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FDG PET/CT is a promising tool for identifying responding/non-responding patients after CAR T-cell therapy. In patients with LBCL undergoing CAR T-cell therapy, usage of pre-therapy FDG PET tumor metrics such as the Metabolic Tumor Volume (MTV), Total Lesion Glycolysis (TLG) and maximum Standardized Uptake Value (SUV max ) have been associated with treatment outcome [10][11][12][13][14][15]. A lower tumor burden and/or lower tumor FDG uptake have been linked to better outcomes.…”
Section: Introductionmentioning
confidence: 99%